2020
DOI: 10.1126/sciadv.abc1176
|View full text |Cite
|
Sign up to set email alerts
|

Ozone affects plant, insect, and soil microbial communities: A threat to terrestrial ecosystems and biodiversity

Abstract: Elevated tropospheric ozone concentrations induce adverse effects in plants. We reviewed how ozone affects (i) the composition and diversity of plant communities by affecting key physiological traits; (ii) foliar chemistry and the emission of volatiles, thereby affecting plant-plant competition, plant-insect interactions, and the composition of insect communities; and (iii) plant-soil-microbe interactions and the composition of soil communities by disrupting plant litterfall and altering root exudation, soil e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
135
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 231 publications
(137 citation statements)
references
References 239 publications
(354 reference statements)
0
135
0
2
Order By: Relevance
“…In 2016, 374,000 and 14,600 non-accidental premature deaths were attributed to air pollution (PM 2.5 and O 3 , respectively) in the EU-28 1 countries [ 24 ]. Air pollution also damages plant ecosystems [ 35 , 49 , 63 ], and surface O 3 is considered as the most detrimental air pollutant in terms of effects on vegetation and biodiversity [ 1 , 52 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, 374,000 and 14,600 non-accidental premature deaths were attributed to air pollution (PM 2.5 and O 3 , respectively) in the EU-28 1 countries [ 24 ]. Air pollution also damages plant ecosystems [ 35 , 49 , 63 ], and surface O 3 is considered as the most detrimental air pollutant in terms of effects on vegetation and biodiversity [ 1 , 52 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent research, serious insect grazing damages on avenue trees were found at relatively low O 3 concentrations (urban centers) in northeast Asia, but such damages were not found on the same species at suburban sites with higher O 3 levels (Takahashi et al 2020 ). Plant–insect communication via biogenic volatile organic compounds (BVOCs) should be considered as a possible explanation for these observations (Agathokleous et al 2020 ; Masui et al 2020 ). Understanding plant–insect communications under changing atmospheric environments may help to conserve healthy forest ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…This GIS-based application is thus a valuable tool to quantify and localize potential negative impacts. Ozone damages can interfere with the vitality of species of plant communities, as well as that of the animals, fungi, bacteria and insects that live in close association with plants or in nearby soils 34 . Changes induced by O 3 impact on many ecological processes, affecting ecosystem services, flows, goods and values.…”
Section: Discussionmentioning
confidence: 99%